2015
DOI: 10.2147/ndt.s77786
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of anxiety sensitivity and psychiatric comorbidities in patients with chronic tinnitus

Abstract: BackgroundTinnitus refers to the objective or subjective perception of a series of sounds most frequently described as ringing in the ear or within the head itself. Anxiety and depressive disorders frequently accompany this complaint. In this study, we aimed to investigate the presence of psychiatric symptoms and the degree of anxiety sensitivity in patients with chronic tinnitus.MethodsFifty patients with chronic tinnitus who had been followed up for at least 6 months or longer were enrolled in this study. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Elevated levels of depression, anxiety, and somatoform disorders have been noted in patients with tinnitus. 42,43 Yet, the association we observe is independent of reported anxiety/panic disorder and depression. Although further study is needed to elucidate biological mechanisms to explain relationships between voice disorders, tinnitus, psychiatric conditions, and possibly migraine headache, greater awareness of voice complaints in people with these conditions may aid in getting people to seek healthcare.…”
Section: Discussionmentioning
confidence: 49%
“…Elevated levels of depression, anxiety, and somatoform disorders have been noted in patients with tinnitus. 42,43 Yet, the association we observe is independent of reported anxiety/panic disorder and depression. Although further study is needed to elucidate biological mechanisms to explain relationships between voice disorders, tinnitus, psychiatric conditions, and possibly migraine headache, greater awareness of voice complaints in people with these conditions may aid in getting people to seek healthcare.…”
Section: Discussionmentioning
confidence: 49%
“…Other survey instruments used were Depressive Tendency Questionnaire (DTQ), Illness Attitude Scale, Obsessive Beliefs Questionnaire-44 (OBQ-44), International Statistical Classification of Diseases 9 (ICD-9), Depression, Anxiety and Stress Scale, and Mini International Neuropsychiatric Interview [13][14][15][16][17][18][19][20][21][22][23] .…”
Section: Resultsmentioning
confidence: 99%
“…These changes, which may influence the occurrence of various psychoemotional disorders and represent a psychological burden, appear to affect the development of tinnitus. Previous studies have also suggested that adolescents are psychologically vulnerable to depression and anxiety, factors that may also contribute to tinnitus . Several psychiatric disorders, such as depression, anxiety, and somatoform disorder, have been reported to be more prevalent in tinnitus patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also suggested that adolescents are psychologically vulnerable to depression and anxiety, factors that may also contribute to tinnitus. 8,25,26 Several psychiatric disorders, such as depression, anxiety, and somatoform disorder, have been reported to be more prevalent in tinnitus patients. This relationship with psychological conditions, including anxiety and depression, was present even after adjusting for neuroticism.…”
Section: Discussionmentioning
confidence: 99%